Pemberdayaan Masyarakat dan UMKM melalui Pengenalan, Pelatihan, dan Pembuatan Produk Digital di Kapanewon Pengasih, Kulon Progo, DIY - Aristya, Ganies Riza; Mif Ardianata Pratama Putra (Direktorat Pengabdian kepada Masyarakat, 2023)
Sidomulyo Village, Pengasih, Kulon Progo Regency in Special Region of Yogyakarta is one of the agrotourism areas that produces a lot of high local food potential. This area is located in the right on the edge of the Menoreh hills with popular local fruit and vegetable cultivation production centers. In addition, local wisdom is still very strong which is felt in every behavior and activity of the people who like to gardening and growing crops in the fields. Some of the superior regional potentials food to be developed are cassava, clove wood, petai and vegetables. Sidomulyo has natural and local potential as well and most of the population opens activities by establishing Micro, Small and Medium Enterprises (MSME). However, this potential requires scientific and technological innovation because it was necessary to compete with production from other regions, lack of innovation and marketing regarding the quality and quality of the products produced. Therefore, there are required to carry out assistance, guidance and training on cooperative relations from farmers with academia, industry and government in order to improve the quality and quality of Indonesian crops through empowering the MSME community and digitizing products. The objectives of this program are to provide intensive and efficient community assistance and empowerment in stages and sustainably, optimizing business opportunities for the Sidomulyo community by utilizing local village potential, increasing marketing of local village products through digital transformation of MSME activities, building village independence through industrial partnership networks to strengthen the potential of a civilized and prosperous Agrotourism village. This program is able to provide information on business opportunities through utilizing local village potential, equipping village communities with digital information systems to market MSME results.